ACTIVITY OF CANONICAL WNT SIGNAL SYSTEM IN HYALINE CARTILAGE ARTICULAR CHONDROCYTES IN PROCESS OF SYNOVIAL JOINT DEVELOPMENT - A.O. Molotkov; S.L. Kuznetsov (Саратовский научно-медицинский журнал, 2009)
Canonical and non-canonical Wnt systems are essential regulators of chondrogenesis and bone development. However, the roles of these systems in synovial joint development are not well studied. To determine if canonical Wnt system is active in developing articular chondrocytes we used immunohistochemistry for в-galactosidase and doublecortin (cell-type specific marker for articular chondrocytes) to double label sections through joint regions of E14.5, E18.5, P10 and adult mice. Here the following results are presented. Canonical Wnt signal system does not work in developing articular chondrocytes at early embryonic stages (E14.5); it is active in the articular chondrocytes at late embryonic stages (E16.5-E18.5) and during postnatal development (P7-P10), but is turned off again in the adult articular chondrocytes. These results suggest that canonical Wnt signaling is being regulated during articular chondrocytes differentiation and joint formation.